Pengaruh Literasi Keuangan, Perilaku Keuangan, Dan Kemajuan Teknologi Terhadap Minat Investasi Di Pondok Pesantren - Mukaromah Mukaromah; Eni Kaharti; Dwi Artati (Jurnal Akuntansi Pajak dan Manajemen (TAJAM), 2026)
T The purpose of this study was to determine the effect of financial literacy, financial behavior, and technological advancement on investment interest. Respondents in this study were male and female students at the Al Quran Al Amin Islamic Boarding School in Pabuaran, Purwokerto. The sample size was 202, calculated using the Slovin formula. A questionnaire was used for data collection. The data analysis used multiple linear regression analysis with SPSS 22.0 (Statistical Package for Social Science). The results indicated that financial behavior and technological advancement had a positive influence on investment interest, while financial literacy had no effect on investment interest.